Investigating the burden of disease dimensions (time-dependent, developmental, physical, social and emotional) among family caregivers with COVID-19 patients in Iran - Sheikhbardsiri, Hojjat; Tavan, Asghar; Afshar, Parya Jangipour; Salahi, Sahar; Heidari-Jamebozorgi, Majid (BMC family practice, 2022)
Background The caregivers of patients with covid-19 face constant responsibilities such as providing personal, health, and social care to family, which can be physically, and emotionally exhausting resulting in a considerable stress burden. Therefore, given the importance of the subject, this study aimed to investigate the burden of disease dimensions (time-dependent, developmental, physical, social and emotional) among family caregivers with covid-19 patients in Iran. Methods This cross-sectional study was conducted one year after the onset of the Covid-19 outbreak in Iran. Family caregivers of Covid-19 patients discharged from the hospitals in Kerman city, Iran, were chosen by simple randomization (n = 1500). Data were collected utilizing a demographic characteristics inventory created by the researcher as well as the Novak and Guest Caregiver Burden Inventory. Descriptive statistics such as mean and standard deviations, frequency, and percentages and analytical statistics such as Kolmogorov-Smirnov, T-test, ANOVA, and Multivariate Linear Regression were used for data analysis using the 20, SPSS Inc., Chicago, IL Software at the level of P < 0.05. Results The results demonstrated that the mean score of family caregiver burden was 2.61[+ or -]0.6 and the severity of this burden was in a moderate range. The finding showed a statistical difference was seen between the family caregiver burden mean score of participants in terms of gender, duration of treatment, age and employed status. The multivariable linear regression model showed demographic variables of caregivers included (female, married, employed, elderly, low income and poor education) had a beneficial influence on family caregiver burden. Conclusion The findings of this study can increase the awareness of health managers, about the level of burden of disease among family caregivers from the covid-19 patients and can help to provide economic, social and psychological support programs for improvement and reducing the burden of disease of caregivers during the covid-19 outbreaks. Keywords: Burden, Family caregiver, COVID-19, Patients, Relevant factors